2006
DOI: 10.1111/j.1742-4658.2006.05119.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Cyp4x1 is a major P450 protein in mouse brain

Abstract: Cytochromes P450 are a superfamily of proteins [1] which are involved in the oxidative metabolism of both foreign and endogenous compounds [2]. The cytochrome P450 4A family is known to be highly induced by peroxisome proliferators in mouse liver [3,4], although there is constitutive expression of one gene [5]. The CYP4A [6], CYP4B [7,8] and CYP4F [9,10] proteins are known to have fatty acid hydroxylase activity, and there is extensive speculation that the formation of hydroxylated fatty acids by cytochrome P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…1C) vehicle controls. The liver expressed CYP2B10, 3A11, 1A2, and 2S1, but not CYP4X1, which is consistent with previous reports of brain-specific CYP4X1 expression in , 2006;Renaud et al, 2011). P450 expression profiles in the brain were region-specific: all five P450 isoforms were expressed in the hippocampus; the cerebellum expressed transcripts for all but CYP1A2, and the cortex expressed only CYP2S1 and CYP4X1 mRNA (Fig.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…1C) vehicle controls. The liver expressed CYP2B10, 3A11, 1A2, and 2S1, but not CYP4X1, which is consistent with previous reports of brain-specific CYP4X1 expression in , 2006;Renaud et al, 2011). P450 expression profiles in the brain were region-specific: all five P450 isoforms were expressed in the hippocampus; the cerebellum expressed transcripts for all but CYP1A2, and the cortex expressed only CYP2S1 and CYP4X1 mRNA (Fig.…”
supporting
confidence: 80%
“…CYP2S1 is abundantly expressed in many extrahepatic tissues (Choudhary et al, 2003) and CYP4X1 is predominantly expressed in the rodent brain (Bylund et al, 2002;Al-Anizy et al, 2006). The data reported herein demonstrate brain region-specific expression of P450s in the rodent brain that is sex-and species-dependent and generally not altered by the classic inducers phenobarbital and dexamethasone under conditions that significantly induce P450 expression in the liver.…”
Section: Downloaded Frommentioning
confidence: 53%
See 1 more Smart Citation
“…Stamou et al (2013) previously reported that CYP4X1 mRNA is equally detectable in the rat liver and brain. Al-Anizy et al (2006) showed the selective expression of Cyp4x1 in the mouse brain, while CYP4X1 mRNA was ubiquitously expressed in adult human tissues (Choudhary et al, 2005). It is of interest that CYP4X1 catalyzes the epoxidation of anandamide, an endogenous cannabinoid, but not arachidonic acid (Stark et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Two isoforms, CYP1A1 and CYP4X1 (Al-Anizy et al, 2006), were detected in the microsomal fraction by immunoblotting (Fig. 8, D and E).…”
Section: Inhibition Of Heme Synthesis Promptly Reducedmentioning
confidence: 99%